Multinationals and Interdependence in Internationalisation Processes - Sérgio Fernando Loureiro Rezende (RAC - Revista de Administração Contemporânea, 2006)
This article deals with interdependence and the internationalisation process of multinationals(MNCs); a topic that has received scarce attention in the literature (e.g. Bell & Young, 1998; Holmet al., 1995). By reviewing the literature on behavioural models of internationalisation, initially, thearticle suggests that MNCs should be regarded as loosely coupled systems in which independenceand interdependence of operations shape how MNCs evolve and organise activities across borders.Subsequently, the article models the internationalisation process of MNCs by highlighting threedimensions that characterise their pattern of evolution - uniformity, direction and rhythm, and laysout three hypotheses on the relationship between these dimensions and interdependence. Thedirection of the relationship is suggested to be negative, i.e., other things being equal, interdependenceis negatively related to uniformity, direction and the rhythm of the internationalisation processes.The article concludes by claiming that the internationalisation of MNCs results from an intricatecombination of independent, yet interdependent, internationalisation processes that evolve invarious spatial and temporal contexts within the MNC network